Development of Science Thematic Learning Media Discovery Learning Model Based on Science, Technology and Society (STM) - Titin Rambe; Kiki Pratama Rajagukguk (Prodi PGMI IAIN Salatiga, 2021)
The aim of research to develop instructional supplement in the form of thematic learning media discovery learning models based STM (science, technology and society) are valid and interesting.The background of this development the lack of use of the media used in teaching natural science is limited to only using textbooks and whiteboards.This development uses the ADDIE model development procedure which includes 5 steps, namely: (1) analyze, (2) design, (3) development, (4) implementation, (5) evaluation. Data analysis technique used is the analysis of qualitative data and quantitative data analysis.Qualitative data analysis was obtained from the validation results of material experts, media experts, learning design experts and teacher. Analysis of quantitative data obtained from questionnaire scores and student learning outcomes tests. Based on data analysis, it shows that the thematic learning media developed are valid and interesting to use in learning.